Study on High School Teachers’ Self-Esteem in Decision Making and Decision Making Styles - ÇORUH, Yaşar; VURAL, Mustafa (Asian Journal of Education and Training, 2019)
This research was carried out in order to investigate self-esteem of high school teachers in Erzurum while making decision and their decision making styles in terms of some variables. In the research, descriptive survey method which aimed to reveal current situation, was used. A total of 160 teachers -of whom 37 are female and 123 are male- working in high schools in Erzurum in 2018-2019 spring semester, participated in the research. In the research, “Melbourne Decision Making Questionnaire” developed by Mann et al. (1998) and adapted to Turkish by Deniz (2004) and “Personal Information Form” developed by researchers were used as data collection tool. Independent Samples T-Test was used in paired comparisons and one-way Anova test was used in multiple comparisons. In multiple comparisons, Tukey-test was used in order to determine between which groups difference existed. Margin of error was considered as 0.05 in this study. As a result of the research, when demographic variables were examined, it was seen that postponer decision making style which is sub-dimension of scale of self-esteem in decision making and decision making styles differentiated according to gender variable of the participants. It was seen that carefully decision making dimension which is sub-dimension of decision making styles scale differentiated significantly according to administrative function variable; and also in age variable, avoidant decision making and panic decision making sub-dimensions which are sub-dimensions of decision making styles scale differentiated significantly. In professional seniority variable, it was determined that avoidant decision making sub-dimension which is sub-dimension of decision making styles scale differentiated significantly.